Collaboration Engineering Approach to Enterprise Architecture Design Evaluation and Selection - Nakakawa, Agnes (Proceedings of CAiSE-DC, 2008)
Before an organisation takes up a particular enterprise ar- chitecture design, there is need to consider and evaluate the possible design alternatives, and then select an appropriate one. This process re- quires a collaborative e ort involving all key stakeholders in order to obtain an `acceptable' solution. Therefore, in this paper we propose the development of a transferable, predictable and repeatable process that supports collaborative evaluation and selection of enterprise architecture design alternatives. To achieve this, we propose the use of collaboration engineering approach. Additionally, a ctitious case of airline mergers is used in order to demonstrate the; problem argued, rationale for solving it, e ective and e cient way of solving it, and applicability of the pro- posed research.
Keywords: Enterprise Architecture; Collaboration Engineering; Evaluation and Selection